Changes in CEO stock option grants: A look at the numbers - Athanasakou, Vasiliki; Ferreira, Daniel; Goh, Lisa (Journal of Corporate Finance, 2022)
We study changes in the number of CEO stock option grants. Despite some evidence of short-term rigidity, the number of options granted changes frequently over time. CEOs of firms with unusual investment patterns subsequently receive fewer stock options as part of their compensation packages. CEOs who hold exercisable deeply-in-the-money options (overconfident CEOs) also receive fewer stock options in subsequent periods. Our results show that past CEO behavior predicts stock option grants. These insights can inform theoretical discussion on option-granting behavior and, more broadly, on the board's re-contracting process.